2019
DOI: 10.4103/psychiatry.indianjpsychiatry_241_18
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and the risk of arthritis: A survival analysis using data from the osteoarthritis initiative

Abstract: Background:Some studies investigated the association between depressive symptoms and arthritis; however, no longitudinal studies have documented the relationship between developing depressive symptoms and the risk of arthritis. Therefore, this study evaluated whether the development of depressive symptoms was associated with an elevated risk of arthritis.Materials and Methods:A survival analysis using Cox regression models was applied to osteoarthritis initiative data obtained over 6 years from adults (n = 3,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…Furthermore, the study found associations between poor mental health (neurological or psychiatric problems, sleep symptoms, poor mental health and in unadjusted analysis probable depression) and SRA, which is consistent with previous results ( 5 , 10 , 18 21 , 26 – 28 ). The association between sleep problems and arthritis may be related to pain at night ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the study found associations between poor mental health (neurological or psychiatric problems, sleep symptoms, poor mental health and in unadjusted analysis probable depression) and SRA, which is consistent with previous results ( 5 , 10 , 18 21 , 26 – 28 ). The association between sleep problems and arthritis may be related to pain at night ( 19 ).…”
Section: Discussionsupporting
confidence: 92%
“…Specific health risk behaviors, such as smoking ( 13 ), low physical activity or sedentary behavior ( 12 , 14 16 ), non-alcohol use ( 17 ) and obesity ( 5 , 8 , 14 , 18 ) have shown to increase the risk of arthritis. Moreover, poor mental health ( 5 , 19 , 20 ), including sleep problems ( 19 ) and depressive symptoms ( 10 , 18 , 21 ), increased the odds of arthritis. Certain chronic conditions, such as hypertension ( 7 , 10 ), cardiovascular disease ( 7 , 22 ), kidney and chronic lung disease ( 7 ), and functional disability ( 10 , 11 , 19 ) were also found to be associated with arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies focusing on the risk of KOA in patients with DS. Previous analyses on the relationship between OA and depression showed similar results to ours, that is, the presence of DS could increase the risk of OA [ 11 , 16 ].…”
Section: Discussionsupporting
confidence: 86%
“…On the one hand, DS is reportedly highly prevalent among KOA patients, and KOA has been cited as a risk factor for developing DS [ 7 11 ]. On the other hand, some studies have shown that patients with DS are more likely to develop arthritis [ 11 , 16 ]. Although many studies have explored the single-directional relationship between KOA and DS, whether the relationship between KOA and DS in both directions coexists in the same group is less verified.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MSK conditions and advancing age are associated with decreased physical function (PF) in older adults, as deterioration of the MSK system function leads to impairments in performing activities of daily living (ADLs) [ 10 ]. Limitations in PF are significant due to their pervasive occurrence and associations with reduced quality of life (QoL), increased risk of disability, falls, depression, and increased healthcare costs [ 11 , 12 ]. Consequently, preserving PF has become a significant public health concern [ 13 ].…”
Section: Introductionmentioning
confidence: 99%